Hierarchal Planning demonstrated in Autonomous Flight; Integration of the Risk-Aware Path Planner with a Sense-And-Avoid Planner on a Black Hawk Helicopter - Goerzen, C.; Takahashi, M.; Whalley, M.; Schulein, G.; Mielcarek, N.; Ogden, W.; Carr, J.; Ott, C.; Thomazios, K.; Waldman, D. (My University, 2023)
A hierarchal planning method with three levels was demonstrated in simulation and in flight on a Black Hawk helicopter. The software was flown on prior occasions and demonstrated the ability to autonomously sense and avoid previously unknown terrain while enroute to a destination. The new mission level software adds the ability to make mission-length plans over a stored terrain map, while simultaneously minimizing user-input risk functions. This system was tested with different levels of pilot input, ranging from simply entering a destination, to replanning while enroute, to adding lateral and longitudinal inputs to influence the flight path and altitude. The addition of this mission level improves the ability of the system to keep to a desired height above ground level, while improving the ability of the pilot or operator to predict the path of the helicopter and time to destination.
Keywords: Unmanned Rotorcraft